Fibrous Osteodystrophy With Facial Hyperostosis Associated With Renal Secondary Hyperparathyroidism In Dogs (Applied Biological Research, 2017)
Renal secondary hyperparathyroidism is a complication of chronic renal failure. It is clinically  characterized by hyperostotic bone lesions such as facial swelling due to the deposition of  unmineralized osteoid by hyperplastic osteoblasts and production of fibrous connective tissue  exceed the rate of bone resorption and increased endogenous levels of parathyroid hormone (PTH)  (Aiello et al., 2015). Although secondary renal hyperparathyroidism and renal osteodystrophy are  well known sequel of chronic renal failure (CRF) but clinically important renal osteodystrophy is  rarely seen in dogs (Nagode et al., 1996, Rusenov et al., 2009; Chand et al., 2012). This paper  presents two cases of fibrous osteodystrophy with facial hyperostosis associated with renal  secondary hyperparathyroidism in dogs.
Keywords: Fibrous; Facial Hyperostosis; Secondary; Hyperparathyroidism; Dogs